Keynes’s Reflections on Entrepreneurship: Of Entrepreneurs and South Pole Explorers - Christian Hecker (Wirtschaftsdienst)
Abstract From Keynes’s point of view, the success of market economies depends not only on government economic policy, but also on the initiatives of forward-looking entrepreneurs. In his opinion, entrepreneurs must distinguish themselves by forming long-term expectations despite omnipresent uncertainty and act accordingly at their own risk. In this way, they contribute significantly to economic stability, human capital formation and technological progress. Today, the importance of entrepreneurship is particularly evident with regard to the development of sustainable business models, whereas orientation towards capital market-based benchmarks can lead to serious misdirection.